Determinants of MDF exports: a panel data analysis - Abdul Samad, Abdul Rahim; Mohd Ashhari, Zariyawati; Othman, Mohd Shahwahid (Canadian Center of Science and Education, 2009)
This study analysed the factors influencing the exports of Medium Density Fibreboard (MDF) with the aid of the panel data approach procedures. The analysis was carried out with the data collected on MDF exports over 10 years (1996–2005) and across 28 countries all over the world using the panel data analysis in estimating the MDF exports with various factors. The result shows that the changes in export quantities of MDF are significantly determined by export price and exchange rate at 1 percent and 5 percent respectively. However, average world GDP is not significant in influencing exports demand of MDF. On the other hand, the Hausman test of the random effects and fixed effects specification give the evidence that the random effects specification is preferable in this model.